Partisipasi Masyarakat Dalam Gotong Royong Untuk Kebersihan Lingkungan Di Desa Dusun Baru 2 Bengkulu Tengah - Ikke Wulan Dari; Ellitro Sandiva Sandiva; Dorizka Vino Lingga; Wulandari Wulandari; Agung Setiawan Pratama; Fauziah Ulfah Nabilah; Fauzi Abdul Rasyid (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
This study aims to explore and enhance community participation in mutual cooperation (gotong royong) for village environmental cleanliness, with a focus on Dusun Baru 2 Village. Gotong royong is an important tradition in many Indonesian communities that plays a significant role in maintaining environmental cleanliness and health. However, community participation in this activity is often influenced by various factors that can affect the effectiveness and sustainability of cleanliness programs. This research uses a qualitative method with a case study approach to understand the dynamics of community participation in gotong royong activities in Dusun Baru 2. Data were collected through in-depth interviews, observations, and analysis of documents related to gotong royong activities. The study also involved focus group discussions to gain perspectives from various community groups. The results of the study indicate that the level of community participation in gotong royong has significantly increased due to several key factors: greater awareness of the importance of environmental cleanliness, support from community leaders, and the provision of adequate facilities. These factors have strengthened the motivation of the community to engage more actively in cleaning activities. Community participation in gotong royong for environmental cleanliness in Dusun Baru 2 Village can be improved through strategies involving education, social support, and facility improvements, ultimately contributing to a cleaner environment and better quality of life.